(untitled) (New Jersey, 2003)
This volume contains reports on state-of-the-art studies relevant to signal detection in important scientific areas such as environmental, industrial and biomedical monitoring. Critical issues in the fields of material development for advanced sensing applications, nuclear techniques using neutrons for humanitarian demining, sensors for biomedical, industrial and environmental monitoring as well as solid state detectors for biomedical applications are confronted with the cross-disciplinary approach of physicists, chemists and biologists.
Keywords: Transducers, biomedical,Medical electronics,Biosensors,Cảm biến sinh học,Điện tử y học,Kỹ thuật y sinh; Congresses,Congresses,Congresses,Tài liệu hội nghị, hội thảo,Tài liệu hội nghị, hội thảo,Tài liệu hội nghị, hội thảo